2015
DOI: 10.1016/j.neurobiolaging.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in large-conductance calcium-activated potassium channels in mammalian circadian clock neurons

Abstract: Aging impairs the function of the suprachiasmatic nucleus (SCN, the central mammalian clock), leading to a decline in the circadian rhythm of many physiological processes, including sleep-wake rhythms. Recent studies have found evidence of age-related changes in the circadian regulation of potassium currents; these changes presumably lead to a decrease in the SCN's electrical rhythm amplitude. Current through large-conductance Ca(2+)-activated K(+) (BK) channels promote rhythmicity in both SCN neuronal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…In central nervous system neurons, BK channels mediate the repolarization and fast afterhyperpolarization of action potentials (Shao, Halvorsrud, Borg-Graham, & Storm, 1999; Womack & Khodakhah, 2002), shape dendritic Ca 2+ spikes (Golding, Jung, Mickus, & Spruston, 1999), and regulate neurotransmitter release at presynaptic terminals (Hu et al, 2001; Raffaelli, Saviane, Mohajerani, Pedarzani, & Cherubini, 2004; Samengo, Curro, Barrese, Taglialatela, & Martire, 2014; Xu & Slaughter, 2005; see Chapter “BK Channels in Neurons” by Barth and Contet). Neuronal BK channels are involved in motor coordination (Sausbier et al, 2004), learning and memory (Matthews & Disterhoft, 2009; Springer, Burkett, & Schrader, 2014; Typlt et al, 2013; Ye, Jalini, Mylvaganam, & Carlen, 2010), the brain’s intrinsic rhythmicity of the circadian clock (Farajnia, Meijer, & Michel, 2015; Meredith et al, 2006; Montgomery, Whitt, Wright, Lai, & Meredith, 2013; Pitts, Ohta, & McMahon, 2006) and respiration (Onimaru, Ballanyi, & Homma, 2003; Zavala-Tecuapetla, Aguileta, Lopez-Guerrero, Gonzalez-Marin, & Pena, 2008; Zhao, Hulsmann, Winter, Dutschmann, & Richter, 2006), frequency tuning of the cochlear hair cell (Fettiplace & Fuchs, 1999), pain modulation (Cao, Chen, Li, & Pan, 2012; Chen, Cai, & Pan, 2009; Waxman & Zamponi, 2014; Zhang, Mok, Lee, Charbonnet, & Gold, 2012), and neuroprotection in pathological conditions (Mancini et al, 2014; Runden-Pran, Haug, Storm, & Ottersen, 2002; Shen, Kishimoto, Linden, & Sapirstein, 2007; Zhang, Xie, et al, 2009). Defects or dysregulation in human neuronal BK channels can cause epilepsy and paroxysmal dyskinesia (Brenner et al, 2005; Du et al, 2005) and are implicated in mental retardation (Deng et al, 2013; Higgins, Hao, Kosofsky, & Rajadhyaksha, 2008), autism (Laumonnier et al, 2006), and schizophrenia (Zhang, Li, Zhou, & Xing, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In central nervous system neurons, BK channels mediate the repolarization and fast afterhyperpolarization of action potentials (Shao, Halvorsrud, Borg-Graham, & Storm, 1999; Womack & Khodakhah, 2002), shape dendritic Ca 2+ spikes (Golding, Jung, Mickus, & Spruston, 1999), and regulate neurotransmitter release at presynaptic terminals (Hu et al, 2001; Raffaelli, Saviane, Mohajerani, Pedarzani, & Cherubini, 2004; Samengo, Curro, Barrese, Taglialatela, & Martire, 2014; Xu & Slaughter, 2005; see Chapter “BK Channels in Neurons” by Barth and Contet). Neuronal BK channels are involved in motor coordination (Sausbier et al, 2004), learning and memory (Matthews & Disterhoft, 2009; Springer, Burkett, & Schrader, 2014; Typlt et al, 2013; Ye, Jalini, Mylvaganam, & Carlen, 2010), the brain’s intrinsic rhythmicity of the circadian clock (Farajnia, Meijer, & Michel, 2015; Meredith et al, 2006; Montgomery, Whitt, Wright, Lai, & Meredith, 2013; Pitts, Ohta, & McMahon, 2006) and respiration (Onimaru, Ballanyi, & Homma, 2003; Zavala-Tecuapetla, Aguileta, Lopez-Guerrero, Gonzalez-Marin, & Pena, 2008; Zhao, Hulsmann, Winter, Dutschmann, & Richter, 2006), frequency tuning of the cochlear hair cell (Fettiplace & Fuchs, 1999), pain modulation (Cao, Chen, Li, & Pan, 2012; Chen, Cai, & Pan, 2009; Waxman & Zamponi, 2014; Zhang, Mok, Lee, Charbonnet, & Gold, 2012), and neuroprotection in pathological conditions (Mancini et al, 2014; Runden-Pran, Haug, Storm, & Ottersen, 2002; Shen, Kishimoto, Linden, & Sapirstein, 2007; Zhang, Xie, et al, 2009). Defects or dysregulation in human neuronal BK channels can cause epilepsy and paroxysmal dyskinesia (Brenner et al, 2005; Du et al, 2005) and are implicated in mental retardation (Deng et al, 2013; Higgins, Hao, Kosofsky, & Rajadhyaksha, 2008), autism (Laumonnier et al, 2006), and schizophrenia (Zhang, Li, Zhou, & Xing, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, under typical physiological conditions, opening of BK channels allows potassium ions to flow outside of the cell leading to membrane repolarization and fast afterhyperpolarization, thus controlling cellular excitability. These aspects are of direct relevance to a new study by Farajnia et al, 2015, reported in this issue of Neurobiology of Aging, on the role of BK channels in aging circadian clock neurons.…”
Section: Introductionmentioning
confidence: 70%
“…Indeed, under typical physiological conditions, opening of BK channels allows potassium ions to flow outside of the cell leading to membrane repolarization and fast afterhyperpolarization, thus controlling cellular excitability. These aspects are of direct relevance to a new study by Farajnia et al, 2015, reported in this issue of Neurobiology of Aging, on the role of BK channels in aging circadian clock neurons.Ó 2015 Elsevier Inc. All rights reserved.Large-conductance calcium (Ca 2þ )-activated potassium (K þ ) channels (BK channels) are important regulators of neuronal excitability in the mammalian nervous system. BK channels are activated by changes in membrane electrical potential and intracellular Ca 2þ concentration, and play a key role in shaping neuronal action potential.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…They are involved in motor coordination [59], learning and memory [28,[60][61][62], circadian rhythm [63][64][65][66], regulation of respiration [67][68][69], hearing [70], and pain [71][72][73][74]. BK channels confer neuroprotection [75][76][77][78].…”
Section: Introductionmentioning
confidence: 99%